ANALYSIS OF COST OF GOODS SOLD CALCULATION IN MSMEs PAHALA GEPREK & CHICKEN - Wicaksono, Achmad; Anwar, Chairil (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This research was carried out with the aim of knowing how the calculation of the cost of goods sold in MSMEs Pahala Geprek & Chicken, and what obstacles experienced by owners in calculating the cost of goods produced. The method used in this study is a qualitative method with a descriptive approach. Research data were obtained through observation and semi-structured interviews with owners and employees. The data obtained is then analyzed descriptively to answer the formulation of the problem raised. The results showed that so far MSMEs Pahala Geprek & Chicken have calculated the cost of goods sold according to the understanding possessed by the owner. The calculation is done simply, namely by adding the cost of raw materials with the cost of employee salaries in one production process. In doing calculations, owners often experience difficulties in determining the cost of goods produced due to relatively fast changes in raw material prices. Keywords: Cost Of Goods Sold, MSMEs, Pahala Geprek & Chicken